The impact of globalization and digitalization on the Phillips Curve - Christian Friedrich; Peter Selcuk (Bank of Canada, 2022)
In this paper, we examine the impact of globalization and digitalization on the Phillips curve in a sample of 18 advanced economies over two decades. Using industry-level data from the World and EU KLEMS databases, we first estimate country-industry-specific Phillips curves for each decade by relating the growth rate of output prices to lagged inflation and an employment gap. We then assess the relative impact of globalization and digitalization on the slope coefficients of these Phillips curves, which represent the sensitivity of inflation to economic slack. We measure globalization by increases in trade and financial integration and digitalization by the use of industrial robots as a share of a country's population. We find that globalization significantly reduces the slope of the Phillips curve, while digitalization has the opposite effect. We also find some evidence that globalization decreases the intercept of the Phillips curve and that digitalization increases it. Evidence for the impact of both trends on employment is less conclusive. When investigating the associated transmission channels for both trends in the context of our slope analysis, we find that the negative impact of globalization on the slope coefficient of the Phillips curve is muted in industries that experience a high growth rate of total factor productivity and that the positive impact of digitalization is muted in industries that have seen high investments in IT capital in the past.
Keywords: E31; E32; F6; O3; 330; Business fluctuations and cycles; Inflation and prices; Labor markets; Trade integration; International topics; Recent economic and financial developments